Aplikasi Berbasis Android untuk Informasi Alat dan Komponen Praktikum di Laboratorium/Bengkel Teknik Telekomunikasi Politeknik Negeri Sriwijaya - Elmerillia, Elmerillia; Lindawati, Lindawati; Salamah, Irma (Patria Artha Technological Journal, 2022)
Laboratories/workshops are the main infrastructure facilities needed for vocational education.Â State PolytechnicÂ of Sriwijaya is one of the vocational universities that has laboratory/workshop facilities in every existing study program. Each laboratory/workshop is equipped with a variety of equipment and practicum components. Existing equipment and components are part of the campus inventory that can be used by all students for practical needs. After making a web-based application for the laboratory/workshop of the Telecommunication Engineering study program as a means to improve the work system of laboratory/workshop technicians, then an Android-based application was also made. This application can be used as a means of information for students and lecturers. This application was created with the aim of providing information about the data of tools and practicum components along with the amount that can be known in real time following the process of taking components and borrowing tools. In addition, other information related to lecture activities is also presented. In the stages of making this application the prototype method is used. The application of the prototype method aims to further optimize application functions according to user needs. With the creation of this application, students of the Telecommunications Engineering Study Program at the Sriwijaya State Polytechnic can find out information on data for practicum needs more easily and can be accessed anywhere. This application has also been tested using black box testing and shows the system results are acceptable and ready for use.